Livestock, land and the environmental limits of animal source-food consumption - Herrero, Mario; Mason-D'Croz, Daniel; Godde, Cécile M.; Palmer, Jeda; Thornton, Philip K.; Gill, Margaret (CGIAR Independent Science and Partnership Council, 2018)
The increase in global consumption of animal source food (ASF) (by more than 40kg/person/year in the last 25 years) has driven livestock production systems in many countries towards intensification. This has significant consequences for land use. Identifying how best to navigate the trade-offs of using land for livestock production depends on understanding what is happening at a local level since there are large regional differences in trends for both supply and demand. Species and production system are also important determinants of land use, but it is the issue of providing sufficient feed for pigs and poultry and for dairy intensification that causes most concern. Producing traditional feeds (grains and soybean meal) competes with arable land used to produce human food. Thus research on increasing the efficient use of feed resources and on identifying new feed resources are both critical to achieve more sustainable livestock production systems, as is policy research on managing demand.